Respuesta :
Answer:
x = 6
Step-by-step explanation:
it states 6 times the quantity x - 2, so the expression would be 6 ( x - 2 ) = 24. first multiply because you cannot add or subtract unlike terms. so 6 multiplied by x and -2, the expression would be (6x - 12) = 24. add 12 to 12 so you cancel the coefficient. but when adding to the constant add to the sum. now it is 6x = 36. since 6x is multiplication, divide 6x by 6 to isolate the variable, but divide the answer, 36 divided by 6 is 6. therefore x = 6. hope this helps